Simplicity and predictability: a phenomenological study of psychological flow in transactional workers - Clapp, Steven R.; Karwowski, Waldemar; Hancock, P. A. (Frontiers in Psychology, 2023)
Psychological flow is a positive experience achieved through a near-balance of task challenge and skill capability, creating a merging of awareness and action and leading to an intrinsically rewarding feeling. Flow has typically been documented in persons who participate in work and leisure activities where they can exercise a large degree of agency over their actions in pursuit of their goals. Semi-structured interviews were conducted with 17 adults whose role is to perform transactional work, which by its nature affords less opportunity for creative execution. Their descriptions of certain work system factors that triggered the onset of flow are documented, as well as what flow felt like to them. Two broad types of flow are described and a connection is made that the present study’s participants achieved one of those flow types. A mapping is performed of the participants’ flow experiences to the nine conventional dimensions of flow. Limitations of the present study and recommended future research are discussed.